Bioconversion of Fruit Processing Waste by Saccharomyces Cerevisiae and its utilization in Feed for Anabas Cobojius - Amrutha,Varshini N. (School of Aquaculture and Biotechnology,KUFOS, 2016)
Abstract- Nonconventional feed resources as aquafeed ingredients are advantageous in being non competitive for human consumption besides being relatively inexpensive. They are often products or byproducts from agriculture / animal husbandry / processing industries. Their utilization also serve as a means of waste utilization and management. Fruit processing waste is an untapped source of energy and protein. It is generated in considerable amounts and is often dumped as waste, leading to sizeable environmental hazards. The use of fruit processing waste in aquafeeds , is hindered by factors like low protein content and low digestibility of carbohydrates. Bioconversion can convert the indigestible, less assimilable form of fruit processing wastes, to a well accepted, easily digested and easily assimilable form. The bioconversion of three different fruit processing wastes, viz., grape , pineapple and papaya by Saccharomyces cerevisiae was taken up . The processed fruit processing wastes were evaluated by incorporating @ 5% inclusion level in diets for Anabas testudineus , having an overall protein content of 40 %. The growth response was assessed by a feeding trial of 64 days duration . A fish meal based diet served as the control. Highest growth of Anabas was recorded in fish fed the pineapple waste based diet and the lowest in the fish meal based control diet. Survival of fish was unaffected by inclusion of fruit processing wastes in the diet. The nutrient content of the fruit wastes was found to be significantly enhanced by fermentation . Dietary inclusion of fruit processing wastes did not have any adverse effect on the organoleptic quality of the test species.